Validating a T1-weighted cine MRI for a 1.5T MR-Linac with temporal resolution appropriate for respiratory motion - Shaffer, Nathan; Dresner, Alex; Ying, Qi; Alberts, Eveline; Kruiskamp, Marijn; Caster, Joseph; Hyer, Daniel; Snyder, Jeffrey; St-Aubin, Joel (Frontiers in Oncology, 2025)
PurposeHigh temporal resolution cine magnetic resonance imaging (MRI) for the 1.5T Elekta Unity MR-Linac system currently relies on a balanced contrast sequence for motion monitoring (MM) and tumor tracking. Despite its high signal-to-noise ratio (SNR), a balanced contrast sequence does not always provide the ideal contrast for tumor imaging in all situations. Thus, the investigation of other contrast high temporal resolution cine MRI sequences is needed.MethodsExperiments were conducted to validate the T1-weighting and SNR on a cine MRI sequence with a frame rate of 4 frames-per-second (fps) and sufficient image quality. A ModusQA Quasar MRI4D motion phantom and Alzheimer’s Disease Neuroimaging Initiative (ADNI) phantom were used to confirm adequate motion tracking, contrast-to-noise ratio (CNR), SNR, and T1 weighting of the new cine MRI sequence. Target tracking success using Elekta’s Comprehensive Motion Management (CMM) algorithm was assessed on in vivo patient images, and the CNR was measured for the patients with liver tumors which are one of the most challenging sites for visualization using the balanced cine MRI sequence.ResultsThe T1-weighted cine MRI sequence exhibited consistent CNR, SNR and T1-weighting over the duration of the scan while maintaining the ability to capture target motion within 1 mm at 4 fps. In-vivo analysis showed that the T1-weighted sequence had an average tracking success rate of 99.3% ± 1.12% versus the 83.3% ± 23.4% success rate of the bTFE sequence using Elekta’s CMM algorithm for all anatomical sites investigated and better CNR compared to the bTFE sequence for all liver tumors investigated.ConclusionThe proposed T1-weighted cine MRI sequence can produce quality T1-weighted images capable of tracking tumor motion over time. This demonstrates the sequence’s potential in motion monitoring tasks as an alternative to the bTFE sequence when necessary.